Regionalization of the atria for 3D electroanatomical mapping, cardiac imaging, and computational modelling: a clinical consensus statement of the European Heart Rhythm Association and the European Association of Cardiovascular Imaging of the ESC - Althoff, Till F.; Anderson, Robert H; Goetz, Christian; Petersen, Steffen E; Díaz, Patricia Martínez; Nijveldt, Robin; Maurovich-Horvat, Pal; Bax, Jeroen; Hussain, Sachal; Schmidt, Constanze; Spicer, Diane E; Sanchez-Quintana, Damian; et al. (Europace, 2025)
This clinical consensus document proposes standardized atrial segments for 3D imaging, electroanatomical mapping and computational modelling, based on anatomical, electrophysiological and clinical considerations, with precise definitions of regional borders allowing for reproducible and automated regionalization. 3D imaging and high-resolution electroanatomical mapping have become an integral part of cardiac electrophysiology and the management of patients with arrhythmias. However, to perform regional quantitative analyses and intra- and inter-individual, as well as cross-modality comparisons, a universal definition of atrial regions and their boundaries is required. While for the left ventricle there is already an established standardized regionalization (AHA 17-segment model), there is no such consensus for the atria. In a multi-disciplinary writing group consisting of cardiologists, cardiac electrophysiologists, cardiovascular imaging specialists, and anatomists as well as specialists in computational cardiac modelling from European Heart Rhythm Association and European Association of Cardiovascular Imaging, a standardized regionalization based on a 15-segment bi-atrial model was elaborated. This clinical consensus document will enable consistent regional analyses and homogeneous data acquisition across different centres and modalities, and may thus have a significant impact on atrial arrhythmia research and personalized treatment approaches based on individual arrhythmia patterns and phenotypes.